Sports Orthopedics - Wippert P-M (Dynamic Media Sales Verlag, 2018)
Psychosocial risk factors significantly influence the genesis of chronic non-specific low back pain (CLBP) as one potential factor in its multifactorial etiology. Therefore, the European Guideline for Diagnostics and Therapy of Back Pain recommend screenings for these factors at an early stage of preventive and therapeutic interventions. Relevant risk factors for the development of CLBP in athletes are pain experience and tolerance, stress, social and medical environment. However, as existing screening tools are not suitable for athletes, there is a need for indices that predict the risk of future back complaints and infer a stratified treatment allocation respecting the response to physical activity.The National Research Networkfor Medicine in Spine Exercise (MiSpEx) is aiming to fill that gap: a biopsychosocial diagnostic tool was developed which supports health care professionals to 1) predict the risk for pain chronicity, disability or extended absenteeism (risk-index, RSI), and 2) recommend a personalized treatment allocation to uni- or multimodal training (prevention-index, RPI-S). Both tools complement the functional indices developed in the MiSpEx network and add to adequate therapeutic strategies that fit individual needs. The present contribution summarizes the current state of research on psychosocial screenings and reports onthe development of RSI/RPI-S.Take Home: RSI and RPI-S can be used to identify biopsychosocial risk factors, which moderate the intervention success. An early screening is essential for athletes personalized care management and is strongly recommended.KEY WORDS: Pain-Diagnostic, Screening, Risk and Prevention Stratification, Personalized Therapy Allocation